Heart involvement in type 1 and type 2 myotonic dystrophy. Insights from a 10-year follow-up study. (25th November 2020) - Fioravanti, F; Golzio, P.G; Carbone, M.L; Panarelli, A; Gagliardi, M; Mazzilli, S; Colopi, M; Ferraro, I; Castagno, D; Giustetto, C; De Ferrari, G.M
Abstract: Background and aim: Myotonic Dystrophy (MD) is the most common inherited muscular dystrophy of the adult. Cardiac manifestation, including arrhythmias and conduction disorders, contributes significantly to the morbidity and mortality of the disease. The transition from a subclinical form of cardiac involvement to potentially life-threating manifestations is highly variable and not yet entirely understood. Aim of this work is to evaluate whether PQ interval (PQi) prolongation could be a reliable marker to predict left and right ventricle impairment and the necessity of a stricter monitoring. Methods: In this retrospective cohort study, we selected all consecutive patients with a confirmed diagnosis of MD (type 1 and type 2) referred to our Centre. We performed clinical, laboratoristic and instrumental assessments (every 3, 6 or 12 months), tailored on each patient's features. Every patient was treated according to the latest guidelines for pharmacological and device therapy. ECG (recorded at 25 and 50 mm/sec), 24h ECG Holter and transthoracic echocardiography were performed at least yearly. Cardiac Magnetic Resonance was requested to better stratify intermediate risk patients to implantable device therapy. Results: A total of 72 patients (age 48±15 years, 39% female) were included in the analysis. Patients with MD type 1 and type 2 were referred to our Centre after a mean period of 12 years (SD ±8 years) from initial diagnosis. After a mean follow-up of 5 years (±4 years), 8 patients died (mean age at death: 60±12.4 years), all of them for respiratory insufficiency. We evaluated PQ interval (PQi) evolution and type I AVB onset. No statistically significant differences emerged when stratifying for type I AVB. Nevertheless, a PQi increase of more than 20 ms during the follow-up (even if PQ <200 ms) is significantly associated with lower values of TAPSE and greater LVEDD, while no differences emerged for LVEF, dyastolic function and other echocardiographic parameters. Moreover, the evolution of PQ interval is associated with an increasing number of supraventricular arrhythmias and a worse prognosis (shorter interval from first cardiac symptom to death, p 0.025), despite optimal medical therapy. Conclusions: Although relatively rare, MD is a challenge for present Cardiologists. How and when to treat those patients is not codified in guidelines or consensus papers. This study suggests PQi variation as a proxy for critical evolution of MD cardiac involvement. ECG and its modification during lifetime seem pivotal for these patients' care, qualifying as a red flag for stringent follow-up. Further evidences, on larger cohorts, are needed to validate these findings. Funding Acknowledgement: Type of funding source: None